2016
DOI: 10.1242/bio.020263
|View full text |Cite
|
Sign up to set email alerts
|

Calcium homeostasis alterations in a mouse model of the Dynamin 2-related centronuclear myopathy

Abstract: Autosomal dominant centronuclear myopathy (CNM) is a rare congenital myopathy characterized by centrally located nuclei in muscle fibers. CNM results from mutations in the gene encoding dynamin 2 (DNM2), a large GTPase involved in endocytosis, intracellular membrane trafficking, and cytoskeleton regulation. We developed a knock-in mouse model expressing the most frequent DNM2-CNM mutation; i.e. the KI-Dnm2R465W model. Heterozygous (HTZ) KI-Dnm2 mice progressively develop muscle atrophy, impairment of contracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…By contrast, Fraysse et al . () reported no difference in peak and time‐to‐peak Ca 2+ transients elicited by field stimulation between WT and KI‐ Dnm2 R465W fibres. The difference may result from their use of the high‐affinity indicator fura‐2, which is kinetically limited and easily saturated under non‐Ca 2+ ‐buffering conditions.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…By contrast, Fraysse et al . () reported no difference in peak and time‐to‐peak Ca 2+ transients elicited by field stimulation between WT and KI‐ Dnm2 R465W fibres. The difference may result from their use of the high‐affinity indicator fura‐2, which is kinetically limited and easily saturated under non‐Ca 2+ ‐buffering conditions.…”
Section: Discussionmentioning
confidence: 91%
“…; Fraysse et al . ). Interestingly, defective intracellular Ca 2+ homeostasis and excitation–contraction (EC) coupling are hallmarks of the centronuclear myopathy resulting from MTM1 deficiency (Al Qusairi et al .…”
Section: Introductionmentioning
confidence: 97%
“…A defect of clathrin-coated vesicles has been previously associated with several human diseases, including cancer, neurologic disorders, and myopathy (71, 72), and remains to be further investigated in centronuclear myopathies. In particular, CME defect may alter membrane content of ion channel, as suggested by alteration of the membrane permeability to calcium, leading to abnormal calcium homeostasis in a mouse model of the DNM2-linked CNM (73). A better knowledge of involvement of clathrin- and caveolin-dependent endocytosis in the pathomechanisms of the DNM2-linked CNM will be of particular interest for identification of specific targets for future development of therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical studies indicated that the DNM2 mutations increase dynamin 2 oligomer stability and GTPase activity [139,140], and in vivo investigations suggested that dynamin 2 is negatively regulated by myotubularin and amphiphysin 2 [141,142]. Knock-in mice harbouring the most common human mutation R465W manifested a mild myopathy with a structural disorganization of the muscle fibers, abnormal contractile properties, and elevated basal Ca 2+ concentrations in the cytosol [143,144]. AAV-mediated expression of the same mutation resulted in abnormal T-tubule structures and a swollen sarcoplasmic reticulum [145], and expression of the severe S619L mutation in zebrafish revealed defective excitation-contraction coupling [146].…”
Section: Mutations In Dnm2mentioning
confidence: 99%